2008
DOI: 10.1007/s10147-007-0735-1
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent rectal GIST resected successfully after preoperative chemotherapy with imatinib mesylate

Abstract: A 60-year-old-man underwent initial resection of a rectal tumor, with a transanal approach, on December 6, 2000. The tumor was diagnosed as a gastrointestinal stromal tumor(GIST) by KIT and CD34 immunohistochemistry. In June 2003, a third recurrence in the rectum was discovered, at the same location as the initial tumor, and he was referred to our hospital. Magnetic resonance imaging (MRI) revealed a tumor 3.0 cm in diameter, compressing the prostate anteriorly. After the oral administration of imatinib mesyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
0
23
0
3
Order By: Relevance
“…After Demetri et al [2] reported the use of imatinib in advanced GISTs, the role of surgical resection in residual disease was highlighted. Induction therapy in patients with locally advanced disease improves resectability and reduces surgical morbidity [8][9][10]. As a result, other series of surgical resection after imatinib use were subsequently reported, and the available pathological data demonstrated a low complete response rate overall.…”
Section: Discussionmentioning
confidence: 96%
“…After Demetri et al [2] reported the use of imatinib in advanced GISTs, the role of surgical resection in residual disease was highlighted. Induction therapy in patients with locally advanced disease improves resectability and reduces surgical morbidity [8][9][10]. As a result, other series of surgical resection after imatinib use were subsequently reported, and the available pathological data demonstrated a low complete response rate overall.…”
Section: Discussionmentioning
confidence: 96%
“…Rectal GISTs account for approximately 2% of all GIST tumors, 0.1% of all colorectal tumors, and have an estimated incidence rate of 0.45 per million persons [6]. However, the clinical course and treatment of GISTs are similar regardless of site of origin.…”
Section: Discussionmentioning
confidence: 99%
“…La potencia del imatinib en terapias de inducción de GIST del recto de alto riesgo se expresa en tasas de respuesta del 80% de los casos tratados, logrando habitualmente una respuesta parcial y una estabilización de la enfermedad, con algunos casos reportados de respuesta patológica completa 5,6 . La positiva experiencia de la neoadyuvancia con imatinib se ha multiplicado en los últimos años, determinando que actualmente sea el tratamiento estándar para los GIST de recto que requieren una cirugía radical o que está en riesgo el aparato esfinteriano [3][4][5][6][7][8][9][10] . En una experiencia de Japón, sobre 29 pacientes tratados en la era pre-imatinib por un GIST rectal, 19 fueron sometidos a una resección abdominoperineal 10 .…”
Section: Discussionunclassified
“…La positiva experiencia de la neoadyuvancia con imatinib se ha multiplicado en los últimos años, determinando que actualmente sea el tratamiento estándar para los GIST de recto que requieren una cirugía radical o que está en riesgo el aparato esfinteriano [3][4][5][6][7][8][9][10] . En una experiencia de Japón, sobre 29 pacientes tratados en la era pre-imatinib por un GIST rectal, 19 fueron sometidos a una resección abdominoperineal 10 . En una revisión reciente de 39 casos atendidos en 2 centros de referencia alemanes en un período de 9 años, se concluye que la neoadyuvancia con imatinib mejora los resultados en cuanto a bordes quirúrgicos libres de tumor, sobrevida libre de enfermedad, sobrevida global y tasas de recidiva local La dosis y duración de la neoadyuvancia con imatinib no está bien definida en la literatura actual, pero en general se acepta que la dosis estándar son…”
Section: Discussionunclassified